Mathematics Teachers' Perceptions of Formative Assessment Implementation Based on the Merdeka Curriculum at SMP Negeri 14 Surakarta - Nugraha, Muhammad Rizky Ardi; Mardiyana, Mardiyana (JagoMIPA: Jurnal Pendidikan Matematika dan IPA, 2026)
This study aims to examine mathematics teachers’ perceptions of formative assessment implementation within the Merdeka Curriculum at SMP Negeri 14 Surakarta. Formative assessment requires teachers to continuously monitor students’ learning progress and adjust instructional strategies accordingly. A descriptive qualitative approach was employed through interviews, observations, and document analysis. The data sources comprised all mathematics teachers of grades VII, VIII, and IX, selected using total sampling to ensure comprehensive documentation of perspectives. The research focused on three dimensions of teacher perception: cognitive (conceptual understanding), affective (attitudes toward assessment), and conative (classroom practices). The findings indicate that teachers generally hold positive perceptions of formative assessment, reflected in their understanding of its function, openness to innovation, and diverse strategies such as quizzes, observations, assignments, and projects. The implementation of formative assessment still encounters challenges, including limited time, student readiness, and facilities. Teachers address these issues through adaptive strategies such as collaboration and flexible assessment design. These findings suggest that successful formative assessment implementation is influenced not only by policy but also by teachers’ perceptions and responses to classroom challenges, thus providing avenues for further research across diverse subjects and educational settings.